(untitled) (Eurasian Journal of Ecology, 2016)
This article presents the results of an evolutionary- morphological features of the genus Sorghum and keys definition of cereals on the structure of the seeds germinate, the development of major organs, types of inflorescences. Also given the keys identify key species and subspecies of wheat, rye, corn.